Combined ab interno trabeculotomy and lens extraction: a novel management option for combined uveitic and chronic narrow angle raised intraocular pressure. (1st February 2016) - Lin, Siying; Gupta, Bhaskar; Rossiter, Jonathan
Abstract : Minimally invasive glaucoma surgery is a developing area that has the potential to replace traditional glaucoma surgery, with its known risk profile, but at present there are no randomised controlled data to validate its use. We report on a case where sequential bilateral combined ab interno trabeculotomy and lens extraction surgery was performed on a 45-year-old woman with combined uveitic and chronic narrow angle raised intraocular pressure. Maximal medical management alone could not control the intraocular pressure. At 12-month follow-up, the patient had achieved stable intraocular pressure in both eyes on a combination of topical ocular antiglaucomatous and steroid therapies. This case demonstrates the effectiveness of trabecular meshwork ablation via ab interno trabeculotomy in a case of complex mixed mechanism glaucoma.